2014
DOI: 10.1098/rstb.2013.0527
|View full text |Cite
|
Sign up to set email alerts
|

An edge-centric perspective on the human connectome: link communities in the brain

Abstract: Brain function depends on efficient processing and integration of information within a complex network of neural interactions, known as the connectome. An important aspect of connectome architecture is the existence of community structure, providing an anatomical basis for the occurrence of functional specialization. Typically, communities are defined as groups of densely connected network nodes, representing clusters of brain regions. Looking at the connectome from a different perspective, instead focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 59 publications
1
57
0
Order By: Relevance
“…de Reus et al [31] investigate how complex network theory can be applied to the analysis of anatomical networks from a link-based perspective, instead of the traditional view of node-based analysis. The authors analyse how links between brain regions are organized in communities and evaluate their robustness introducing a new class of edge removal metrics.…”
Section: Overview Of This Issuementioning
confidence: 99%
“…de Reus et al [31] investigate how complex network theory can be applied to the analysis of anatomical networks from a link-based perspective, instead of the traditional view of node-based analysis. The authors analyse how links between brain regions are organized in communities and evaluate their robustness introducing a new class of edge removal metrics.…”
Section: Overview Of This Issuementioning
confidence: 99%
“…The approach of Irimia and Van Horn to quantify how lesioning an individual connection affects the global network structure is an elegant way to shift focus from nodes to edges and provides insight in the role or importance of the disrupted connection (de Reus et al, in press). …”
Section: Lesioning Connectionsmentioning
confidence: 99%
“…Functional studies have revealed that the precuneus is involved in a variety of functions associated with self-perception and visual imagery [Lou et al, 2004; Land, 2014], processing of spatial working memory [Wallentin et al, 2006, 2008], and memory retrieval (recognition of familiar faces [Gobbini and Haxby, 2007; Lee et al, 2013]; episodic memory [Vannini et al, 2011]; recognition memory [Hassabis and Maguire, 2009] autobiographical memory [Freton et al, 2014]). Moreover, the precuneus is a functional core of the Default Mode Network, a set of interconnected cortical areas that is active at rest [Raichle et al, 2001; Tomasi and Volkow, 2010; Utevsky et al, 2014], and it is a crucial hub of large-scale brain connectivity [Hagmann et al, 2008; Li et al, 2013; Reus et al, 2014]. Therefore, the precuneus is a region that is both structurally and functionally central for integrating multiple neural systems, and is comprised of different sub-regions involved in distinct cognitive functions [Margulies et al, 2009; Zang and Li 2012].…”
Section: Introductionmentioning
confidence: 99%